2014
DOI: 10.3389/fgene.2014.00218
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between sugar and hormone signaling pathways modulate floral signal transduction

Abstract: NOMENCLATURE The following nomenclature will be used in this article: Names of genes are written in italicized upper-case letters, e.g., ABI4.Names of proteins are written in non-italicized upper-case letters, e.g., ABI4.Names of mutants are written in italicized lower-case letters, e.g., abi4.The juvenile-to-adult and vegetative-to-reproductive phase transitions are major determinants of plant reproductive success and adaptation to the local environment. Understanding the intricate molecular genetic and physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 162 publications
(236 reference statements)
1
65
0
2
Order By: Relevance
“…The participation of ABI3 as well as ABF2 and ABF4 transcription factors has been demonstrated in sugar signal transduction, either dependent or independent of hexokinase [6,28,36,63]. In addition, more recent results indicated the interaction of cytokinins, gibberellins, jasmonic acid, salicylic acid, and brassinosteroids with sugar pathways during plant development [57,103,104]. It was suggested that the function of HXK1 is dependent on the presence of brassinosteroids, which might act downstream of HXK1 to regulate hypocotyl elongation in A. thaliana in darkness (in a glucose-dependent reaction) [104].…”
Section: Receiving and Transmitting The Signals Triggered By Sugarsmentioning
confidence: 98%
See 3 more Smart Citations
“…The participation of ABI3 as well as ABF2 and ABF4 transcription factors has been demonstrated in sugar signal transduction, either dependent or independent of hexokinase [6,28,36,63]. In addition, more recent results indicated the interaction of cytokinins, gibberellins, jasmonic acid, salicylic acid, and brassinosteroids with sugar pathways during plant development [57,103,104]. It was suggested that the function of HXK1 is dependent on the presence of brassinosteroids, which might act downstream of HXK1 to regulate hypocotyl elongation in A. thaliana in darkness (in a glucose-dependent reaction) [104].…”
Section: Receiving and Transmitting The Signals Triggered By Sugarsmentioning
confidence: 98%
“…For example, the delivery of sucrose to the A. thaliana mutant, phyA, characterized by late flowering, accelerated the formation and flowering of the inflorescence stem [58]. As was recently reported, the crosstalk between sugar signaling and photoreceptors (as well as hormones) is required for proper transmission of the flowering signal [31,57].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Excellent reviews on the role of sugar signaling in plant development have been published in recent years. Most of these focus on specific signaling pathways or developmental processes, for example, on flowering and interaction with hormones (Matsoukas, 2014a), growth (Lastdrager et al, 2014), T6P (O'Hara et al, 2013), T6P and SnRK1 (Tsai and Gazzarrini, 2014), hexokinase (Granot et al, 2014), miRNAs (Yu et al, 2015), or SnRK1 and TOR (Baena-González and Hanson, 2017). The whole life cycle of the plant is considered here (Box 1), including step changes (such as floral transition) as well as more gradual processes (such as leaf senescence).…”
mentioning
confidence: 99%